2019
DOI: 10.1055/s-0039-3400951
|View full text |Cite
|
Sign up to set email alerts
|

Micronized Dehydrated Human Amnion Chorion Membrane Injection in the Treatment of Knee Osteoarthritis—A Large Retrospective Case Series

Abstract: Osteoarthritis (OA) of the knee is a leading cause of chronic pain and disability in the United States. Current treatment options primarily target OA symptoms reserving surgical intervention and knee replacement for those who fail conservative measures. With average age of patients with knee OA decreasing, regenerative treatment approaches to reduce symptoms, increase quality of life, and delay the need for surgical intervention are increasingly sought. Human amniotic membrane contains growth factors and cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Despite little evidence to support matrix regeneration, these results indicate the potential for imparting a chondroprotective effect and attenuating degeneration in vitro . This study substantiates previous clinical [ [4] , [5] , [6] ] and pre-clinical evidence suggesting μdHACM treatment improves the outcomes associated with OA. Specifically, μdHACM attenuated the onset of surgically-induced OA in a medial meniscal transection (MMT) rat model [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite little evidence to support matrix regeneration, these results indicate the potential for imparting a chondroprotective effect and attenuating degeneration in vitro . This study substantiates previous clinical [ [4] , [5] , [6] ] and pre-clinical evidence suggesting μdHACM treatment improves the outcomes associated with OA. Specifically, μdHACM attenuated the onset of surgically-induced OA in a medial meniscal transection (MMT) rat model [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…Micronized dehydrated human amnion/chorion membrane (μdHACM; MiMedx Group, Inc.), an injectable advanced biologic, is explored as an alternative solution to the shortcomings of traditional treatments. Previously published animal studies [ 3 ] and early outcomes in clinical studies [ [4] , [5] , [6] ] have demonstrated success using μdHACM for OA, notably resulting in symptomatic improvements and pain reduction; however, the molecular mechanisms by which this is accomplished is unknown. μdHACM is a PURION® processed allograft, which retains regulatory proteins inherent to native amniotic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical case series have recently been published in support of the use of particulate amniotic membrane ECM-based materials (amnion, chorion, umbilical cord, amniotic fluid) to treat OA ( Mead and Mead, 2020 ; Natali et al, 2022 ; Alden et al, 2021 ; Bennett, 2019 ; Castellanos and Tighe, 2019 ; Farr et al, 2019 ; Vines et al, 2016 ). Four of the studies specifically addressed knee OA, though they were relatively small preliminary studies (6, 20, 25, and 42 qualifying patients), and indicated that single injections with suspensions of either amniotic membrane, amniotic membrane combined with umbilical cord, or amniotic membrane combined with amniotic fluid may help reduce knee pain and improve function in moderate knee OA in the short term ( Mead and Mead, 2020 ; Natali et al, 2022 ; Castellanos and Tighe, 2019 ; Vines et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One large retrospective case series has been published on the use of injectable micronized dehydrated human amnion/chorion membrane (dHACM) alone, and it included review of 100 knees treated with the product. Patient-reported outcome scores (including pain, daily living, sports/recreation, and quality of life categories increased over time up to 6 months ( Alden et al, 2021 ). One multi-center level I randomized controlled trial that enrolled 200 knee OA patients concluded that treatment with single injection of an amniotic membrane particulate/amniotic fluid suspension was superior to hyaluronic acid and saline at 3 and 6 months in terms of pain relief and improved function.…”
Section: Introductionmentioning
confidence: 99%
“…For patients who are taking antiplatelet and anticoagulation medications, they may not be able to receive autologous platelet-rich plasma (PRP) injections [ 6 ]. Other treatment options include the application of physical modalities, the wearing of insoles, and the injection of other injectants such as micronized dehydrated human amnion/chorion membrane (mdHACM) [ 8 , 9 ]. Researchers are continuously searching for nonsurgical disease-modifying options for the treatments of knee OA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%